Teaching an Old Shell New Tricks: Extracting DNA from Current, Historical, and Ancient Mollusk Shells. (20th January 2021) - Martin, Kelly R; Waits, Lisette P; Parent, Christine E
ABSTRACT: The use of unconventional DNA sources has increased because the acquisition of traditional samples can be invasive, destructive, or impossible. Mollusks are one group for which novel genetic sources are crucial, but methodology remains relatively undeveloped. Many species are important ecologically and in aquaculture production. However, mollusks have the highest number of extinctions of any taxonomic group. Traditionally, mollusk shell material was used for morphological research and only recently has been used in DNA studies. In the present article, we review the studies in which shell DNA was extracted and found that effective procedures consider taxon-specific biological characteristics, environmental conditions, laboratory methods, and the study objectives. Importantly, these factors cannot be considered in isolation because of their fundamental, sometimes reciprocal, relationships and influence in the long-term preservation and recovery of shell DNA. Successful recovery of shell DNA can facilitate research on pressing ecological and evolutionary questions and inform conservation strategies to protect molluscan diversity.